GENERAL PREVALENCE AND FORMS OF MANIFESTING THE RELIGIOSITY AMONG THE POPULATION IN THE OHRID-STRUGA REGION (Religious dialogue and cooperation, 2021)
Today, as a result of the failure of socialism, we arefacing a period of numerous big changes in society, which are ofeconomic, political and social nature. In addition, these changesare accompanied by changes in the value priorities of the socialvalue system. More precisely, people are exposed to influencesof social, political and cultural events, so it is difficult for them toadapt. In such a situation, religion offers a philosophy of life that iscompatible to specific confession. Ethnicity and religion are basiccohesive factors in multicultural and multiconfessional areas likeours. There are tendencies of individuals and groups to equatenationality with religion. Religion as one of the key factors ofhuman consciousness influences not only the building of spiritualsystem and the social value system, but also the way of life. Losingself-confidence in solving the important tasks in life, man tries tofind help, and it is precisely religion that is the right direction tolook for it. It is very important to emphasize the activities of theconfessional communities which insist on attracting attention withtheir organizational structures and filling the gaps that other socialinstitution and organization left empty. The social changes occurringin the late 1980s and early 1990s brought about by the failure ofsocialism are changing the social role of religion. We live in a worldcharacterized by processes of desecularization or sacralization. Thepercentage of those who have declared themselves non-religiousin the past is almost equal to those who have declared themselvesreligious in the period after the 1990s. This reversal or change ofattitude towards religion, which is characterized by increasedreligiosity among the entire population, is an inspirational groundfor the study of religion. In this research, the subject of investigationwas the religiosity of the population in the Ohrid-Struga region,a region that represents ethnic and religion heterogeneousenvironment. The two most important religious organizations are the Macedonian Orthodox Church - the Ohrid Archbishopric andthe Islamic Religious Community. The target group is consisted ofpeople older than 18. The results obtained by the research showthe influence of religiosity, which is at a very high level, on the valueorientations of the population in the Ohrid-Struga region.
Keywords: religion; religiosity; religious organizations; value orientations; religious tolerance